Egungun Festival as a Tourist Attraction to Foreigners and Its Impact on the Oke Ayedun People - Folorunso Paul Olorunsola; Olayinka Olabimpe Ojo; Adedolapo Adenike Adewuyi (Britain International for Academic Research (BIAR-Publisher), 2023)
This paper delves into the captivating world of the Egungun festival as celebrated in the vibrant town of Oke Ayedun, Ekiti. The Egungun festival holds immense cultural significance, intertwining the realms of the living and the departed through intricate rituals, vibrant performances, and ancestral homage. The article provides an overview of the proposed research, highlighting the festival’s historical context, its role in community identity, the symbolism of masquerades, and the transformative experiences it offers to participants and observers.